Determination of Plasma Osteopontin and Serum Inhibin B in Pregnant Women with Preeclampsia - Mehde, Atheer A; Mehdi, Wesen A; Mustafa, Seenaa A (Al-Nahrain Journal of Science, 2018)
Pre-eclampsia is a multisystem disorder of pregnancy, which complicates 3%-5% of pregnancies in the world .The present study deals with estimation of levels of Osteopontin, Inhibin B, protein, albumin, globulin and Alb./Glb. ratio in forty five Pregnant Women with Preeclampsia in comparison with thirty healthy Pregnant Women. In Pregnant Women with Preeclampsia, the level of Osteopontin and Inhibin B were significantly higher as compared to the normal subjects [p